2021
DOI: 10.1186/s12873-021-00417-3
|View full text |Cite
|
Sign up to set email alerts
|

Disaster safety assessment of primary healthcare facilities: a cross-sectional study in Kurdistan province of Iran

Abstract: Background Kurdistan province of Iran is among disaster prone areas of the country. The Primary Health Care facilities in Iran deliver health services at all levels nationwide. Resiliency and flexibility of such facilities is important when a disaster occurs. Thus, evaluating functional, structural, and non-structural aspects of safety of such facilities is essential. Methods In this cross-sectional study, the instrument used to evaluate four secti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 21 publications
1
6
0
Order By: Relevance
“…Personnel training is often an issue in implementing emergency and disaster management. This is in line with other research on PHCs in Iran, where the HSI index for the training and training personnel aspect is considerably low [57]. The results of the MCA also show that from all aspects of the assessment using the HSI instrument, the PHCs in all assessment provinces tended to be closer to category "B" and required improvement.…”
Section: Functional Aspectsupporting
confidence: 90%
“…Personnel training is often an issue in implementing emergency and disaster management. This is in line with other research on PHCs in Iran, where the HSI index for the training and training personnel aspect is considerably low [57]. The results of the MCA also show that from all aspects of the assessment using the HSI instrument, the PHCs in all assessment provinces tended to be closer to category "B" and required improvement.…”
Section: Functional Aspectsupporting
confidence: 90%
“…Only a few studies have reported on the HSI of hospitals in different countries; a study analyzing primary care centers in a province of Iran, assessing disaster safety with a maximum of 100 points, found that these facilities had an overall average score of 28.7 (low safety in functional, structural, and non-structural aspects). 33 Another study conducted in 15 hospitals in Indonesia found that their HSI had a value of 0.544 (equivalent to Category B). 34 In contrast, in a study of six Australian hospitals, their HSIs were found to have high scores.…”
Section: Discussionmentioning
confidence: 99%
“…The increase in the burden of hospital patients and the need for timely and effective provision of medical services by hospitals highlight the importance of hospital preparedness during RTAs, especially those resulting in mass casualty incidents (MCIs) [ 6 ]. In addition, to improve preparedness for emergencies and in line with international commitments, countries are encouraged to improve their healthcare systems and strengthen national capacity for emergency health management, crisis response, and flexibility in healthcare systems [ 7 ]. Considering the role of hospitals as vital components of the healthcare system in responding to disasters and emergencies to ensure service continuity and effective delivery [ 8 , 9 ], the World Health Organization emphasizes the importance of hospital preparedness and response capacity [ 9 – 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies in this country have shown that RTAs impose a significant economic burden on Iran’s gross domestic product per capita and health expenses per capita [ 3 ]. The focus of this research is on Kurdistan province, located in west of Iran, with an area of 28,235 square kilometers [ 7 ] and a population of nearly one and a half million people [ 19 ], which accounts for about 1.7% of the country’s area [ 7 ]. The topography, geographic and ethnic diversity, and border location of this province have made it susceptible to various natural and human disasters [ 7 , 20 ].…”
Section: Introductionmentioning
confidence: 99%